Diabetes Medication Reconciliation at Hospital Discharge - Shah, Nandi (J Endocr Soc, 2021)
Background: During hospital discharge, patients are at high risk for medication discrepancies as they transition from hospital to home. This study aims to evaluate the prevalence of medication errors at hospital discharge for diabetes medications in patients who received an endocrinology consultation for diabetes and explore interventions to improve the accuracy of discharge medication reconciliation. Methods: All patients (n=3018) who received an endocrinology consultation for diabetes at a tertiary care medical center from October 2017 to December 2019 were included. A retrospective chart review was performed to collect the following information on each patient: primary service from which the patient was discharged, hospital site, month and year of discharge date, and whether each patient’s medication reconciliation for diabetes medications at hospital discharge was in agreement with the inpatient diabetes team’s recommendations. Patients who were discharged on medications discordant from those recommended by the inpatient diabetes service were subcategorized into three groups: 1) one medication incorrect 2) more than one medication incorrect and 3) the primary service did not notify the consult team of patient’s discharge or request final recommendations for diabetes medications prior to discharge. Based on the findings of this study, an educational intervention was implemented in November 2019 to the Hospital Medicine services regarding diabetes discharge medication reconciliation. Results: Of the 3018 patients who received an endocrinology consultation for diabetes at a tertiary university medical center, 2279 patients (76%) were discharged on correct medications, 165 patients (5%) were discharged with one incorrect medication, 443 patients (15%) were discharged with more than one incorrect medication, and 121 patients (4%) were discharged without final discharge recommendations from the diabetes service. There was no significant variation based on discharging service or month of the year. After an educational intervention was implemented in November 2019 to the Hospital Medicine service on the existence and use of a comprehensive diabetes discharge order set, the percentage of patients discharged on correct medications improved to 92% (11/12 patients) compared to prior 81% (44/54 patients). Conclusion: Despite detailed discharge medication recommendations including patient education detailing the recommended regimen by the endocrinology diabetes service, a significant number of patients were discharged by providers across all services on diabetes medications discrepant with the diabetes service’s recommendations. Educational efforts improved the rate of correct medications at discharge on the Hospital Medicine service, and additional educational interventions with other services may be helpful in improving medication reconciliation accuracy.